2016
DOI: 10.5267/j.ijiec.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid algorithm for stochastic single-source capacitated facility location problem with service level requirements

Abstract: Facility location models are observed in many diverse areas such as communication networks, transportation, and distribution systems planning. They play significant role in supply chain and operations management and are one of the main well-known topics in strategic agenda of contemporary manufacturing and service companies accompanied by long-lasting effects. We define a new approach for solving stochastic single source capacitated facility location problem (SSSCFLP). Customers with stochastic demand are assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…As a result, they showed that the proposed heuristic outperforms the current method and leads to a considerable reduction in inventory. Extra research (de Kok, 1985;Tempelmeier, 2007;Selçuk & A gralı, 2013;Jaggi et al, 2016;Salemi, 2016;Oblak et al, 2017) has also been carried out to address diverse aspects of backordering and service-level constraint of fabrication systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they showed that the proposed heuristic outperforms the current method and leads to a considerable reduction in inventory. Extra research (de Kok, 1985;Tempelmeier, 2007;Selçuk & A gralı, 2013;Jaggi et al, 2016;Salemi, 2016;Oblak et al, 2017) has also been carried out to address diverse aspects of backordering and service-level constraint of fabrication systems.…”
Section: Introductionmentioning
confidence: 99%
“…With a help from an analytical model and the Lagrangian multiplier technique, they were able to simultaneously derive the optimal order quantity, lead time, and number of shipments to each customer per cycle. Additional studies (Fergany, 2016;Rakyta et al, 2016;Jindal & Solanki, 2016;Jaggi et al, 2016;Qu & Ji, 2016;Salemi, 2016;Oblak et al, 2017;van Rhyn & Hancke, 2017) have also been conducted to explore the effects of permitted backlogging and service level constraint on fabrication systems. Nevertheless, little attention has been paid to exploration of joint effects of machine failure, backorder of permissible shortage, rework and scrap on stock replenishing decision, and the present work is set to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptations to the global production network are strategic decisions because of their long-term impact on companies. Many decisions like the opening of new sites are difficult to revise and are connected with many unknowns due to the long planning period [5]. Therefore, thorough decision-making is essential.…”
Section: Introductionmentioning
confidence: 99%